The Potential. Developing the athlete`s performance possibilities - Brooks. C. L. (Techniques Magazine, 2012)
Every athlete has a specific level of performance potential. Relative to other competitors their age, this may be high, moderate, or low depending on a whole host of factors. The variables we will discuss in this paper include: • Genetics versus training. • Physical capacity and exploitation capability. • The adaptation process. • How things can go wrong.